Streamflow estimation at ungauged site using wavelet group method of data handling in Peninsular Malaysia - Basri, Badyalina (2014)
This study investigates the ability of wavelet group method (WGM) of data handling conjunction model in the estimation of flood quantiles in ungauged sites in Peninsular Malaysia. The conjunction method was obtained by combining two methods, discrete wavelet transform and group method of data handling. Comparison between the WGM model, group method (GM) of data handling model, wavelet regression (WR) model and linear regression (LR) model were done. To assess the effectiveness of this model, 70 catchments in the province of Peninsular Malaysia were used as case studies. The performance of WGM model was compared with the conventional LR, GM and WR models using various statistical measures such as the mean absolute error, root mean square error and Nash-Sutcliffe coefficient of efficiency. Jackknife procedure was required for the evaluation of the performance of the four approaches. The jackknife procedure was needed to simulate the ungauged sites. The results of the comparison indicate that the WGM model was more accurate and perform better than the traditional LR, GM and WR models. Thus, WGM model is a promising new method for estimation of flood quantiles in ungauged sites